Effect of t (11; 19) (q23; p13.1) Gene on Proliferation and Apoptosis of SGC 7901 Gastric Cancer Cell Line - Zhou, Hai-Bo; Ma, Wang-Qian; Shao, Li-Ming (International Journal of Innovative Research in Medical Science, 2018)
Objective: To investigate the effect of t (11; 19) (q23; p13.1) gene on proliferation and apoptosis 0f SGC 7901 gastric cancer cell line Methods: Gastric cancer cell line SGC 7901 cells were selected to transfect t (11; 19) (q23; p13.1) gene. MRNA levels of t (11; 19) (q23; p13.1) in each group were regulated after 24, 48 and 72h byRT- PCR. Cell proliferation was determined MTT assay. The apoptosis status of the SGC 7901 cells was detected TUNEL method. Immunohistochemical staining evaluated the expression of apoptotic genes Bcl-2 and Bax. Results: The MTT assay showed that t (11; 19) (q23; p13.1) decreased the proliferation of SGC 7901 cells. TUNEL method detected t (11; 19) (q23; p13.1) could improve apoptosis of SGC 7901 cells. In addition, t (11; 19) (q23; p13.1) could improve the expression of apoptotic gene Bcl-2 and reduce the expression of apoptotic gene Bax. Conclusion: T (11; 19) (q23; p13.1) gene can inhibit gastric cancer cell proliferation and improve apoptosis of gastric cancer cell.